IMPLICATURES FOUND IN CONVERSATIONS DONE BY THE MAIN CHARACTERS OF THE ICE AGE 4 MOVIE - LEATEMIA, MAYA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Cartoon movie is a funny entertainment which has a story line like a reallife. People like this kind of movie because it is supported by motion and soundeffect so they need less effort to enjoy it. In this study, the writer proposed twoproblems of the study, (1) What kinds of implicatures are found in conversationsamong the main characters in The Ice Age 4 movie? and (2) What are the intended meanings of the implicatures found in conversations among the main characters in The Ice Age 4 movie?This study uses qualitative approach in relation to the use of clear andsystematic description about the phenomena of implicatures in conversations done by the main characters in Ice Age 4 Movie. Descriptive textual analysis is applied in this study to analyze conversations of the main characters of The Ice Age 4 movie. The data of this study are the utterances which contain implicatures produced by the three main characters, furthermore the writer collects the data according to Miles and Huberman’s theory (1994).There are fifteen utterances which contain implicatures in conversationsdone among the three main characters. All the utterances have the maxims which are being flouted. They are maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner. This study reveals that there are threeconventional implicatures and twelve conversational implicatures. Those twelveconversational implicatures consist of five generalized implicatures that consist of four scalar implicatures and one indefinite implicature, and seven particularized implicatures.The writer suggests the next researchers who want to conduct a similarresearch to understand more about implicature. Besides understanding theconventional and conversational implicatures, they can also use another theory to make the study more complete like Relevance Theory by Sperber and Wilson. It is expected that their study can be more complete and understandable.Kata Kunci: Conversational Implicature, Conventional Implicature, animated cartoon